Formação continuada de professores de matemática: um estudo sobre a práxis docente no Programa Gestar II na Bahia - Silva Filho, Analdino Pinheiro (2013)
This study discusses the teaching praxis embodied in the proposed political-pedagogical of continuing training of GESTAR II Mathematics Program, implemented in Bahia, since 2005 to 2012. This study is a qualitative approach and has the general objective Analyze how teaching praxis is understood within the political-pedagogical proposal of the Program GESTAR II in Mathematics in Bahia. It has as analytic categories of ideas and praxis (VÁZQUEZ, 2011) of professionalism (SACRISTÁN, 1999). Accordingly, it’s investigated the continued training of mathematics teachers from a critical analysis of the "arena" in which educational policy is made and how the principles and precepts are engendered by it are represented in the training model proposed. It also discusses the concepts of continuing education from the ideas of writers such as Giroux (1997), Fusari (1997), Nóvoa (1995) and Pimenta (2009, 2011). The used methodological tools were document research, the literature search and questionnaire. Based on these instruments, It was performed an entire reading back of the observed in the international agreements and national education, on policy, pedagogical and curricular multilateral organizations, the MEC and the Department of Education of Bahia; the assumptions in political, theoretical and pedagogical that substantiate the GESTAR II; under perception about the praxis of six teachers teaching Mathematics into the GESTAR II Program, as well as the authors that support the theoretical framework of this research. The data collected showed that the conception of teacher praxis, via political-pedagogical proposal of continuing education of teachers in Bahia, still finds limits, such as: It has been unable to form a true and meaningful sense of praxis and teaching has promoted significant structural changes and functional work aimed at personal, social and professional teacher developing. The study indicates the need to understand that the teaching activity is not external to psychological, cultural and social conditions that teachers experience in the social dynamics of their lives.